2001
DOI: 10.1177/135910530100600307
|View full text |Cite
|
Sign up to set email alerts
|

Article Predictors of Wellbeing and Autonomy Before and After Geriatric Rehabilitation

Abstract: The aim of this study was to explore changes in the correlational association between predictors (i.e. sociodemographics, subjective health, social support, anxiety and coping) and outcome measures (i.e. subjective wellbeing and autonomy) before and after rehabilitation treatment. The data came from a sample of 90 patients (mean age 78.8 years; 84 percent female; 37 percent stroke, 44 percent fracture, 19 percent other diagnoses), who were assessed before and after rehabilitative treatment. Results revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
12
0
2
Order By: Relevance
“…However, the present findings underscore the notion that, while health plays an important role in SWB, self-rated health and SWB may not be synonymous concepts and may not be predicted by the same factors nor predict outcomes to the same extent. Our findings are consistent with previous work that found the associations between SRH and other measures of SWB (e.g., life satisfaction) to be modest and mediated by consequences of poor health [21,22]. Our findings differ from an earlier study where SWB (i.e., life satisfaction) did not predict adverse clinical outcomes after adjusting for poor SRH and other relevant factors [23].…”
Section: Subjective Well-being At Baseline and Adverse Clinical Outcomessupporting
confidence: 54%
“…However, the present findings underscore the notion that, while health plays an important role in SWB, self-rated health and SWB may not be synonymous concepts and may not be predicted by the same factors nor predict outcomes to the same extent. Our findings are consistent with previous work that found the associations between SRH and other measures of SWB (e.g., life satisfaction) to be modest and mediated by consequences of poor health [21,22]. Our findings differ from an earlier study where SWB (i.e., life satisfaction) did not predict adverse clinical outcomes after adjusting for poor SRH and other relevant factors [23].…”
Section: Subjective Well-being At Baseline and Adverse Clinical Outcomessupporting
confidence: 54%
“…One study reported high correlations between the Trier Scales on coping with illness subscales and other variables, with r values .0.8. 51 The coping domains of information seeking and search for affiliation correlated highly with subjective well-being and autonomy, providing supporting evidence of the validity of this scale. Overall, there was little evidence of construct validity for the coping scales used in the studies reviewed, and the correlations between the subscales of the coping scales and other variables reported were generally weak.…”
Section: Coping Measures and Domainsmentioning
confidence: 74%
“…State anxiety and behavioural coping, played no predictive role at admission into geriatric rehabilitation and became the strongest predictors of autonomy at discharge [9]. Extrovert personality measured by Eysenck's Personality Inventory and active coping strategy predicted improved ADL functions among former stroke patients at the three years follow-up stage [10].…”
Section: Introductionmentioning
confidence: 99%